Technical Processing Wastewater Treatment Plant of Balangan Regional Public Hospital, Balangan Regency, South Kalimantan, Indonesia: Study Waste Waterwastewater Spreading in Water Sources - Rijali Noor; Nova Annisa; Muhammad Syahirul Alim; Hafiizh Prasetia (Comment: an International Journal of Community Development, 2022)
Wastewater produced from the Balangan Regional Public Hospital activities can be dangerous to the environment because it can damage the soil, pollute groundwater, and cause contamination in river water. Because of this contamination, the transmission of diseases caused by bacteria found in wastewater was made feasible. Therefore, it is crucial to consider hospital environmental health while managing waste to ensure that it complies with specified hospital wastewater quality standards. This can be done by managing wastewater appropriately and under criteria. Using the Watershed-Based Model, these community development activities provide insight into how wastewater generated by the Balangan Regional Public Hospital could be distributed and transformed (physical, chemical, and biological). Based on the study's findings, it was discovered that the number of contaminants that can be tolerated would be affected by variations in river water discharge measured at different places. The bigger the water outflow, the greater the capacity to receive pollutants. Large water outflow has the potential to thin the contaminants even further. Rainfall in the Balangan River Basin will impact river water discharge and pollution levels